DEMAND OF VEGETABLE PROTEIN: POTENTIALITIES AND DIFFERENTIAL OF MACAÚBA BRANS (REVIEW) - Grande, Salvador Carlos (2016)
Some of the challenges of sustainable development aim to meet the needs of the population growth, as the demand for food and renewable fuels. Concomitantly, the inef iciency of agro industrial production processes results in huge waste and underutilization of this potential in dif erent raw materials. Many waste generated in the production chain and food processing plants are still a source of protein, fiber and carbohydrates, however, this potential nutritional status is little used for human consumption, and most of the times, intended for animal feed or production of fertilizers. In this sense, this review aims to point out not only the nutritional potential, with respect to the composition of proteins associated with the waste generated in processing oilseeds, highlighting the of macaúba fruits but also provide technological strategies for recovery of proteins in waste, in order to make them available in a sustainable way.